Study of CYP3A5 genetic polymorphism in Vietnamese Kinh ethnic group - Nhung, Vu Phuong; Ton, Nguyen Dang; Ha, Nguyen Hai (Academia Journal of Biology, 2020)
Cytochrome P450 3A5 (CYP) belongs to the CYP3A cluster, which encode for several enzymes involved in metabolism of various drugs, endogenous substrates as well as exogenous compounds. Among the four genes of CY3A cluster, CYP3A5 plays an important role in pharmacogenetics since this enzyme metabolizes over 30% of the clinically prescribed drugs. The inter-individual variability in clearance of CYP3A substrates mainly depends on the genetic factors. In the present study, after collecting peripheral bloods samples from 100 unrelated healthy Kinh ethnic group in Vietnam, Sanger sequencing was used in order to determine the CYP3A5 variants responsible for enzyme activity alteration (*3, *6, *8 and *9). It was shown that CYP3A5*3 is the most prevalent variant with 67.5%, in which a haft of individuals carrying *3 were homozygous for this allele. In contrast, the variants *6, *8 and *9 were not found the study subjects. The data observed in current study would support dosing of drugs that metabolized by CYP3A5 and thereby increase treatment outcome.